ANALISIS RASIO KEUANGAN TERHADAP KINERJA KEUANGAN PADA PT ADARO ENERGY Tbk PERIODE 2018-2022 - Dian Sinar Simamora; Nurlela Silaban; Tuberta Rosviani Mendrofa; Grace Anastasia Octavia Lumban Toruan; Rizki Sipayung (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
Using the financial ratio method from 2018 to 2022, this study aims to find out the economic ratio analysis of the financial performance of PT Adaro Energy Tbk. Current ratio (CR), Debt to debt-to-equity ratio (DER), and Return on Asset (ROA). The data used in this study is from the financial statements for 2018-2022. The quantitative descriptive data analysis used aims to provide an overview of the financial position. The liquidity ratio of PT Adaro Energy Tbk is seen from the average CR (Current Ratio) of 188.84 % over the last five years, which indicates that the liquidity ratios of PT ADARO Energy Tbk are not good. The solvency ratio of PT Adaro Energy Tbk is also seen from the average DER (Debt to Equity) of 188.84%. This shows that the financial ratio of PT Adaro Energy Tbk is not good. According to the average DER (Debt to Equity Ratio) in the last five years, the solvency ratio of PT Adaro Energy Tbk is 144.46%. This shows that the ratio of debt to equity of PT Adaro Energy Tbk is not good. With an average return on assets (ROA) of 11.94% over the last five years, PT Adaro Energy Tbk has a higher profitability ratio than the industry average. Keywords: financial performance, financial statements financial ratios, liquidity ratios, solvency ratios, and profitability ratios